Perubahan Sosial Akibat Modernisasi Pada Komunitas Petani Padi Di Gampong Lingom Kabupaten Aceh Besar - Hanim , Zakiratul; Nurdin, Ibnu Phonna (Prodi Sosiologi Universitas Mataram, 2024)
The presence of agricultural modernization in people’s lives changes the tradisional agricultural process to modern agriculture, apart from that it also causes social changes among farming communities when using modern machines. This research aims to analyze and describe the beginning of modernization in the rice farming community in Gampong Lingom, Indrapuri District, Aceh Besar Regency. This research focuses on the social change that occurs. This research uses modernization theory according to Raillon (1989) which discusses transformation in the economic, sosio-cultural and environmental fields. This research is qualitative research with a case study method, data collection techniques using observation, interviews, documentation, and 9 informants, informants were selected using the purposive sampling method. The research results show that the presence of agricultural modernization can make farmers’ work easier, the agricultural process is fast, saves agricultural coast and also does not use human labor, but it also has several negative impacts on the rice farming community, which can be seen from the economic sector which includes changes in livehood patterns, systems bartering is starting to disappear, the environmental sector which includes rice productivity is decreasing and land degradasion is occurring and the socio-cultural sector which includes khanduri blang, cok uroe customs and confrontations between brokers. There are also social problems is role of kejruen blang is not optimal.